Getting to the “COR” - Halbesleben, Jonathon R. B.; Neveu, Jean-Pierre; Paustian-Underdahl, Samantha C.; Westman, Mina (Journal of Management, 2014)
Proposed as a theory of motivation, the basic tenet of conservation of resources (COR) theory is that humans are motivated to protect their current resources and acquire new resources. Despite its recent popularity in the organizational behavior literature, several criticisms of the theory have emerged, primarily related to the central concept of resources. In this review, we address concerns regarding the conceptualization, conservation, acquisition, fluctuation, and measurement of resources. We highlight gaps in the COR literature that can be addressed by integrating research from other areas of psychology and management. In this manner, we hope to push the COR literature forward by resolving several concerns and providing suggestions for future research that might address other concerns.